Blood specimen rejection pattern in chemical pathology laboratory of Hospital Sungai Buloh from July to December 2016 / Nur Ain Ismail - Ismail, Nur Ain (2017)
In clinical laboratory testing, it can be divided into three phases which are pre- analytical, analytical and post-analytical phase. Among all these three phases, it had been found out that most errors happened in pre-analytical phase. As its effect, these will lead to specimen rejection in laboratories which may cause delay in getting patient diagnosis as well as delaying the treatment for patient. Therefore, this study was conducted in order to focus on pattern of specimen rejection and major causes that lead to specimen rejection. Thus, a retrospective study had been conducted by collecting data of specimen rejection along with causes that lead to its rejection. Total number of rejected blood samples in chemical pathology laboratory of Hospital Sungai Buloh had been collected from July to December 2016 including reasons for rejection. The data was then analyzed statistically in order to find any significance pattern of rejection in laboratories and to find most common reason that lead to blood specimen rejection. After analyzing the data, there was an increasing pattern in first 3 months and decreasing pattern in the last 3 months. There was also significant increase in month of September where number of rejected specimens was 1056 in total. Other than that, hemolysis was found as the major factor that causes rejection of blood specimen. In conclusion, sample handling must be done with full of care in order to avoid errors in clinical laboratory testing.